Cryoprservation of Saccharomyces Cerevisiae Yeast Cells Without Conventional Ñryoprotective Agents - Ponomareva, Viktoriya L.; Kuleshova, Larisa G. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):175.